PENGADAAN TANAH UNTUK PROYEK PEMBANGUNAN MAMMINASATA DAN DAMPAKNYA DI PEDESAAN - Muhammad Ridha (BHUMI: Jurnal Agraria dan Pertanahan, 2014)
The research is aimed at answering three related questions, either directly or indirectly on the program of large-scaleland acquisition on Mamminasata Program in South Sulawesi. These questions are: 1) How does the space structure change afterMamminasata project on land acquisitions at three villages: Samata, Pacci’nongang and Romang Polong?; 2) How does the processand dynamic land acquisition at three village take place?; 3) How does the possibility of conflict take place after the project wasdone. Those questions will be answered by descriptive qualitative research method. The result shows that there was a correlationbetween large scale land acquisition on Mamminasata program with spatial change, the rise of land and extensive agrarian conflict.Keywords: development program, Mamminasata, spatial change, land acquisition.